GeOC presentation (EN). Amman, Jordan: The International Center for Agricultural Research in the Dry Areas (ICARDA). - Graziano, Valerio (2017)
Presentation on "Global Geo-Informatics Options by Context" web GIS, developed as part of the project 'Impact Evaluation of SLM Options to Achieve Land Degradation Neutrality'.